A cross-sectional study on the assessment of adherence to cardiovascular medications in Sudan heart center - Adil A. Mahmoud; Ali Awadallah Saeed; Asim Ahmed Elnour; Osama Nasreldin E. M.; Vineetha Menon; Semira Abdi Beshir; Sami Fatehi Abdalla; Abuelnor Mohammed; Mohamed Baraka; Fahad T. Alsulami; Yousef Saeed Alqarni; Nadia Al Mazrouei; et al. (PLoS ONE, 2025)
Background Non-adherence to cardiovascular medications is a global problem with clinical, economic, and humanistic consequences. Investigation of this problem may open the road for proper management of cardiovascular diseases. Objective Our objectives were to assess the level of adherence to, and to examine factors influencing adherence to, cardiovascular medications in subjects visiting a heart center in Sudan. Methods We have conducted a cross-sectional study that assessed adherence to cardiovascular medications among subjects visiting outpatient cardiac clinics in a heart center-Khartoum State, Sudan. The validated Adherence to Refills and Medication Scale (ARMS) tool was used to assess the level of medication adherence. A score of >16 was used as a cut-off point to categorize surveyed patients into non-adherent (e.g., 17–48) and adherent (e.g., 12–16) in ARMS. Descriptive statistics (frequencies and percentages) and inferential tests such as One-Way ANOVA and Binary regression were used for data analysis. Results A total of 255 subjects were enrolled in this study. Slightly more than half the respondents were males (54.5%) and their ages ranged between (51–60 years), and have no insurance coverage (58%). Most of the subjects were married (60.4%), were from Khartoum-State (67.8%), and were unemployed (77.6%). About 39.6% had primary education while 34.5% had secondary (34.5%) education. Diabetes (56.1%) and hypertension (45.5%) were common among the study population. The results showed a high non-adherence prevalence rate (97.6%). The cited reasons for non-adherence include forgetfulness and the costs of refilling medications. Education and age were associated with the level of adherence. Those with high non-adherence behaviors were the more educated, younger and old patients, those not employed, and those having comorbid diseases. Conclusion The results generally showed a high level of non-adherence to cardiovascular medications, necessitating interventions to support patients’ adherence.